2015
DOI: 10.7554/elife.08890
|View full text |Cite
|
Sign up to set email alerts
|

Many lncRNAs, 5’UTRs, and pseudogenes are translated and some are likely to express functional proteins

Abstract: Using a new bioinformatic method to analyze ribosome profiling data, we show that 40% of lncRNAs and pseudogene RNAs expressed in human cells are translated. In addition, ~35% of mRNA coding genes are translated upstream of the primary protein-coding region (uORFs) and 4% are translated downstream (dORFs). Translated lncRNAs preferentially localize in the cytoplasm, whereas untranslated lncRNAs preferentially localize in the nucleus. The translation efficiency of cytoplasmic lncRNAs is nearly comparable to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
565
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(594 citation statements)
references
References 56 publications
27
565
1
1
Order By: Relevance
“…Several groups have recently applied machine-learning algorithms to mammalian Ribo-seq data to detect AUG uORFs (Fields et al 2015;Ji et al 2015;Calviello et al 2016). Although these studies identified hundreds of uORFs, they did not test them for function or address NCC uORFs.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have recently applied machine-learning algorithms to mammalian Ribo-seq data to detect AUG uORFs (Fields et al 2015;Ji et al 2015;Calviello et al 2016). Although these studies identified hundreds of uORFs, they did not test them for function or address NCC uORFs.…”
Section: Discussionmentioning
confidence: 99%
“…41 Apart from allosteric regulation, it is also feasible that short proteins could negatively regulate enzyme activities by competing with enzymatic substrates for binding to the active site. While direct evidence is still missing, it is intriguing to speculate that pseudogenes, about one-third of which were recently shown to be translated into proteins of various lengths in human cells, 15 might provide a source for such competitive inhibitory peptides. 60 Future work might also reveal that some of the newly discovered proteins have specific enzymatic activities themselves.…”
Section: Short Proteins As Regulators Of Protein-protein Interaction mentioning
confidence: 99%
“…New translated regions have not only been identified in transcripts thought to be non-coding, but also upstream of a large fraction of protein-coding ORFs (so-called upstream ORFs, uORFs). 4,[13][14][15][16][17][18][19][20][21] These usually short translated ORFs were likely missed in previous mutagenesis screens due to their small size, and remained un-annotated in genome annotations due to their small size and lack of evidence for codingness. [22][23][24] In analogy to the term 'pervasive transcription', 25 this unforeseen prevalence of short ORF (sORF) translation has spurred the notion of 'pervasive translation'.…”
Section: Introductionmentioning
confidence: 99%
“…There are additional pipelines that include 3-nt periodicity as part of the analysis (18,19). The 3-nt periodicity of Ribo-seq has been leveraged to identify novel small ORFs in zebrafish embryos and mouse/human cells (6,15,18,19).…”
mentioning
confidence: 99%
“…Furthermore, computational pipelines have been developed to identify translated ORFs by interrogating 3-nt periodicity specifically, including "ORF score" (a summary statistic that tests if one particular reading frame is enriched in Ribo-seq by comparing to a uniform distribution) (6) and "RiboTaper" (a spectrum analysis that determines whether footprints on a transcript display 3-nt periodicity) (15). There are additional pipelines that include 3-nt periodicity as part of the analysis (18,19). The 3-nt periodicity of Ribo-seq has been leveraged to identify novel small ORFs in zebrafish embryos and mouse/human cells (6,15,18,19).…”
mentioning
confidence: 99%